Relapse in anorexia nervosa: a systematic review and meta-analysis. Issue 6 (November 2018) - Berends, Tamara; Boonstra, Nynke; van Elburg, Annemarie
Abstract : Purpose of review: Relapse is common in patients with anorexia nervosa. The aim of this study is to systematically review the existing literature on relapse in anorexia nervosa. Recent findings: A systematic literature search was conducted in PubMed, PsychInfo and CINAHL published up to April 2018. Of the 1527 studies screened, 16 studies were included in the present review. Summary: This analysis shows that, of the patients included in this review, 31% relapsed after treatment. The highest risk of relapse is during the first year after discharge and this risk continues for up to 2 years. An overview was made of all factors significantly associated with a higher risk of relapse, resulting in the following four clusters: eating disorder variables, comorbidity symptoms, process treatment variables and demographic variables. Future research on relapse prevention is necessary to further unravel the mechanisms that might lead to relapse.